EEE! It's ethical environmental economics: a review - Naschold, Isabel P., author; Kroll, Stephan, advisor; Chenarides, Lauren, committee member (Colorado State University. Libraries, 2026)
Ethical considerations are critical for rigorous economic research, yet the field of environmental economics exhibits varying levels of consensus and implementation of ethical guidelines. This literature review investigates the current state of ethical guidelines within environmental economics. The primary purpose is to determine how researchers are currently guided by ethical principles, why these guidelines are sometimes not implemented, and to clarify best practices for research rigor and equitable policy design. The review analyzes literature across three core subfields: contingent valuation (CV) and non-market valuation, research on incentive-based policy, and environmental justice (EJ). The methodology involved searching academic databases, with the initial CV section search aided by the Elicit AI tool, followed by traditional citation-chasing for all three sections. Each category was analyzed based on how ethical concerns manifest in data collection, policy implementation, and measurement. The review finds a common theme: the essential importance of community input. For CV studies, ethical rigor is achieved through community involvement in survey design to mitigate potential bias and cultural gaps. For incentive-based policies, the consensus favors carbon taxes as the most ethical tool, provided tax revenues are redistributed equitably to affected communities. In EJ research, ethical measurement requires deliberate spatial aggregation and acknowledgment of how policy outcomes can lead to gentrification or disproportionately benefit wealthier populations. Barriers to ethical implementation often stem from prioritizing epistemological rigor over community engagement and a lack of resources. The paper concludes that ethical research in environmental economics is fundamentally about building stronger, mutually beneficial relationships between researchers and the communities they study. By prioritizing community input and equity alongside efficiency, researchers can improve the quality and effectiveness of their work, ensuring policy recommendations drive change that benefits the most vulnerable populations.
Keywords: Honors Thesis